PENGAJUAN SOAL DITINJAU DARI GAYA KOGNITIF FIELD DEPENDENT DAN FIELD INDEPENDENT - Evin Marisa; Siti Nuriyatin; Nurina Ayuningtyas (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2021)
This study aims to describe the analysis of students abilities in question submission in terms of cognitive style field dependent (FD) and field independent (FI). Qualitative descriptive study is type of this research. The selection of research subjects was carried out using 2 tests, namely GEFT (the Group Embedded Figures Test) and a test problem posing. Then from this study the selected subjects consisted of four students, namely two students who had a field dependent cognitive style and two students who had a field independent cognitive style. The ability to understand information (questions), field dependent subjects and field independent subjects described accurately. what is known in his own language. The ability to plan a question-making, field dependent and field independent subjects clearly describe the plan for making questions. The ability to make questions, field dependent subjects and independent field subjects are able to make questions with a flat image according to the material. The ability to check questions, field dependent subjects and field independent subjects solve them by entering the right formula and using the correct calculations. As well as checking the answers to the questions he made very carefully the correctness of the answers he had completed.